The pseudo-events paradox : how pseudo-events flood the Philippine press and why journalists don't recognize it - Edson C. Tandoc Jr (2010)
Daniel Boorstin introduced in 1961 the concept of "pseudo-events" of false realities which he said had been flooding the American Press (Boorstin, 1961). Four decades later, testing his concept on the Philippines Press, this study finds that his observation still holds true. This exploratory study, using content analysis of 2,330 news articles and a survey of 100 jornalists, offers the concept of the "pseudo-events paradox". Though journalists perceive there are more spontaneous events in their work and that these have better chances of being published, published news articles about pseudo-events actually outnumber those based on spontaneous events. News articles based on pseudo-events are usually obtaine through personal interviews, press conferences and press releases, methods Boorstin had associated with pseudo-events and which journalists admitted were among the easiest data gathering methods.Politicians, found to be among the most active stagers of events, were also the most quoted sources.